Can stress and coping profiles predict athletes` emotions and performance in competition? Analysis of profiles at competitions throughout the sporting season - Lepers, E.; Levillain, G.; Martinent, G.; Nicolas, M. (International Journal of Sport and Exercise Psychology, 2025)
During sporting competitions, athletes are confronted with stress. To cope with stress, they resort to a number of strategies that affect both their emotions and their performance. The aim of this study was to identify the different stress and coping profiles, their transitions during the sports season, and their effects on emotions and performance. A sample of 385 athletes (88 women and 297 men, Mage = 20, SD = 6) from various disciplines completed the Coping Function Questionnaire, Sport Emotion Questionnaire, Attainment of Sport Achievement Goal Scale and a visual analogue scale to assess stress level. These questionnaires were completed over five measurements across the competitive season. Latent profile transition analysis (LPTA) revealed the existence of three stress and coping profiles, stable over time: Low stress and coping (low use of all strategies to cope with the demands of the situation), Moderate stress and task-oriented coping (the most appropriate profile because the subjective performance scores are the highest), Moderate stress and high coping (strong use of all strategies to cope). Depending on the profile, emotions and perceived performance scores differed. Specifically, performance and the intensity of emotions such as joy and excitement tended to increase, while the intensity of emotions such as anger and dejection decreased depending on the coping strategies used. Knowing that athletes with moderate stress levels using a combination of coping strategies were characterised by better perceived performance may help practitioners to better prepare athletes and encourage the use of multiple coping strategies.